Experimental determination of the valence band offsets of ZnGeN2 and (ZnGe)0.94Ga0.12N2 with GaN. (25th March 2021) - Karim, Md Rezaul; Noesges, Brenton A; Jayatunga, Benthara Hewage Dinushi; Zhu, Menglin; Hwang, Jinwoo; Lambrecht, Walter R L; Brillson, Leonard J; Kash, Kathleen; Zhao, Hongping
Abstract: A predicted type-II staggered band alignment with an approximately 1.4 eV valence band offset at the ZnGeN2 /GaN heterointerface has inspired novel band-engineered III-N/ZnGeN2 heterostructure-based device designs for applications in high performance optoelectronics. We report on the determination of the valence band offset between metalorganic chemical vapor deposition grown (ZnGe)1− x Ga2 x N2, for x = 0 and 0.06, and GaN using x-ray photoemission spectroscopy. The valence band of ZnGeN2 was found to lie 1.45–1.65 eV above that of GaN. This result agrees well with the value predicted by first-principles density functional theory calculations using the local density approximation for the potential profile and quasiparticle self-consistent GW calculations of the band edge states relative to the potential. For (ZnGe)0.94 Ga0.12 N2 the value was determined to be 1.29 eV, ∼10%–20% lower than that of ZnGeN2 . The experimental determination of the large band offset between ZnGeN2 and GaN provides promising alternative solutions to address challenges faced with pure III-nitride-based structures and devices.